2018
DOI: 10.1155/2018/7909467
|View full text |Cite
|
Sign up to set email alerts
|

Shade Trees Spatial Distribution and Its Effect on Grains and Beverage Quality of Shaded Coffee Trees

Abstract: Shading coffee trees has gained importance, especially among smallholders, as an option to improve the products' quality, therefore acquiring place at the specialty coffee market, where consumers are willing to give bonus for quality. This work aims to evaluate the influence of shade trees' spatial distribution among coffee trees' agronomic characteristics, yield, and beans and cup quality of shaded coffee trees. The experimental design consisted of completely randomized blocks with six repetitions and four tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Altitude, latitude and the climate define the growth and maturation of fruits in the plant (Paula Carvalho et al, 2014). Silva Neto et al (2018) confirmed the relation between beverage quality and bean formation time, when observing a strong influence of shading and the coffee plant phenology on the beverage sensory characteristics. Zaidan et al (2017) stated that there is influence of varieties and environments on coffee quality.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Altitude, latitude and the climate define the growth and maturation of fruits in the plant (Paula Carvalho et al, 2014). Silva Neto et al (2018) confirmed the relation between beverage quality and bean formation time, when observing a strong influence of shading and the coffee plant phenology on the beverage sensory characteristics. Zaidan et al (2017) stated that there is influence of varieties and environments on coffee quality.…”
Section: Introductionmentioning
confidence: 54%
“…According to Silva Neto et al (2018), in tree-shaded coffee plants, the phenological stage is accelerated, with early flowering, resulting in faster matured beans. Martins et al (2015) observed the influence of climatic conditions on coffee productivity and quality.…”
Section: /7mentioning
confidence: 99%
See 1 more Smart Citation
“…Shading plantation can provide a number of important benefits to coffee. It has been found to reduce air temperature, soil, and leaf surface temperature as well as the thermal amplitude (Da Silva Neto et al, 2018). It also protects coffee plants from strong winds, rains, or hail and reduces the effect of biennial bearing, and improve and maintain soil fertility by way of returning large amounts of leaf litter to the underneath soil, that is, shade trees can be a valuable source of organic matter, nitrogen fixation, while retaining soil moisture (Beer et al, 1998).…”
Section: Advantages Of Shade For Coffee Productionmentioning
confidence: 99%
“…One known constraint on shade‐grown coffee sales is the perception of the taste—one of the most important factors influencing shade coffee consumption (Commission for Environmental Cooperation, 1999; Messer et al., 2000). Although shade‐grown coffee is generally regarded as higher quality than sun‐grown coffee (Muschler, 2001; Da Silva Neto et al., 2018) some consumers list the taste of shade‐grown coffee as both a reason for and against purchasing it (Messer et al., 2000). Further, bird‐friendly coffee sales may also be hindered by the common constraints on purchasing organic coffee certifications, including perceived inconvenience of purchasing the coffee and consumers’ distrust of the coffee certifications and labels (Davies et al., 1995; Hughner et al., 2007; O'Donovan & McCarthy, 2002; Zanoli & Naspetti, 2002).…”
Section: Introductionmentioning
confidence: 99%